The ABCs of Gene Cloning - Wong, Dominic W. S. (Springer International Publishing, 2018)
Clear and concise, this easy-to-use book offers an introductory course on the language of gene cloning, covering microbial, plant, and mammalian systems. It presents the nuts and bolts of gene cloning in a well-organized and accessible manner. Part I of this book outlines the essentials of biology and genetics relevant to the concept of gene cloning. Part II describes common techniques and approaches of gene cloning, ranging from the basic mechanics of DNA manipulation, vector systems, process transformation, to gene analysis. Part III & IV present application technologies of major impact in agriculture, biomedicine, and related areas. The ABCs of Gene Cloning, Third Edition contains updates including a tutorial chapter on gene-vector construction, methodologies on exome sequencing in finding disease genes, revised topics on gene therapy and whole genome sequencing, new developments for gene targeting and genome editing, as well as the current state of next generation sequencing. With more than 140 illustrations, this new edition provides an invaluable text for students and anyone who have interest in gaining proficiency in reading and speaking the language of gene cloning.